Optimization and characterization of biosurfactant production by Bacillus subtilis isolates towards Microbial Enhanced Oil Recovery applications - Pereira, J. F. (2013)
Biosurfactant production by three Bacillus subtilis strains (#309, #311 and #573) isolated from Brazilian crude oils was optimized based on different carbon and nitrogen sources. The lowest surface tension values were obtained using sucrose containing media for the three isolates. Biosurfactants produced by each strain were characterized by Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (1HNMR), and Matrix-assisted laser desorption ionizationtime of flight mass spectrometry (MALDI-TOF). The chemical characterization showed that the three isolates produced very similar mixtures, containing C13-, C14- and C15-surfactin, although in different proportions. The structure of surfactins produced by the three strains was shown to be in good agreement with their surface-activities. The interfacial-activities of the biosurfactants were characterized and compared with chemical surfactants. Furthermore, the application of biosurfactants and chemical surfactants in oil recovery was evaluated. The results obtained showed that biosurfactants have better interfacial-activity and oil recovery efficiency than common chemical surfactants, thus being more attractive to be applied in Microbial Enhanced Oil Recovery.